2012
DOI: 10.2223/jped.2216
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association study of tumor necrosis factor-alpha with sepsis and septic shock in Thai pediatric patients

Abstract: Objectives: To evaluate the association between the genetic polymorphism of the tumor necrosis factor-alpha (TNF-α) gene and the development of sepsis and septic shock in Thai pediatric patients and to investigate the clinical impacts of TNF-α polymorphisms in this population. Methods:To perform this genetic association study, a prospective analysis of pediatric patients (age < 18 years) with clinical sepsis/ septic shock was conducted. All clinical data were collected by pediatric intensive care experts, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
(25 reference statements)
0
18
0
Order By: Relevance
“…Among them, 12 studies were conducted in Asian populations , 10 in Caucasian populations , and four in mixed populations (more than two ethnic groups) . A majority of studies (80.8%) were performed in adult populations, only four studies in pediatric populations . The type of sepsis included sepsis (n = 15), severe sepsis (n = 3), septic shock (n = 2), and mixed patient groups (n = 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 12 studies were conducted in Asian populations , 10 in Caucasian populations , and four in mixed populations (more than two ethnic groups) . A majority of studies (80.8%) were performed in adult populations, only four studies in pediatric populations . The type of sepsis included sepsis (n = 15), severe sepsis (n = 3), septic shock (n = 2), and mixed patient groups (n = 6).…”
Section: Resultsmentioning
confidence: 99%
“…In 2010, Teuffel et al performed a systematic review and meta‐analysis and found that TNF ‐α −308G/A polymorphism was associated with sepsis but not sepsis mortality . Since 6 years have passed and more evidence has been published , it is of great value to update the results. Moreover, the study conducted by Teuffel et al only focused on TNF‐α −308G/A polymorphism .…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of TNF-α and IL-1β have been correlated with septic shock and increased risk of bacterial infections. [12][13][14][15] High levels of circulating IL-6 are commonly implicated in inflammatory diseases, tissue damage, uncontrolled activation of macrophage cells, and increased rate of infections. 12,13,16 These observations may provide insight to the fulminant action of Ab-acquired pneumonia in which the patient typically presents with bacteremia and septic shock leading to death.…”
Section: Cr3 Ismentioning
confidence: 99%
“…TNF-α has been involved in sepsis immunodepression through increased apoptosis [18]. The significant contribution of the TNF-α to the pathology of the inflammatory response generated the idea of a possible genetic determinism of its circulating levels and hence of sepsis risk and evolution [12,13,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The single nucleotide polymorphism (SNP) at position -308 in the promoter region of the TNF-α gene is the most studied in sepsis and has been associated with higher transcription rates of the cytokine and, more often than not, with an increased risk of sepsis [13,18,32,36,37].…”
Section: Introductionmentioning
confidence: 99%